Arduous Path to Constitutionalism: Serbian Constitutional Developments in the First Half of the Nineteenth Century - Popović, Dragoljub (Pravni zapisi, 2019)
Serbian nation building began in 1815, with the achievement of home rule. The Sultan granted autonomy to the Serbs in 1830 and the first constitutional ideas emerged immediately within the framework of designing autonomous institutions by the Serbs themselves. Those ideas were prevailingly modern, although the authors of the constitution drafts for the Serbian vassal state, who remain unknown to date, did not properly understand some western concepts. That was evident in the contacts with foreign diplomats. The National Assembly adopted the first constitution in 1835. It was a mixture of the liberal ideas of its drafter with the aspirations of the Prince who favoured unchecked exercise of power. The foreign powers were dissatisfied with the 1835 Constitution and urged the Prince to suspend it only a month after the adoption. In 1838 the Sultan gave a constitution to the vassal state of Serbia. It provided for oligarchy as the form of government and remained in force for decades. Neither of the two constitutions relied on a liberal settlement. However the ideas were slowly developing as regards the pillars of constitutionalism – the separation of powers, fundamental rights and the rule of law. When teaching of law set foot in Serbia in the 1840s the constitutional concepts exposed in the university were far ahead of the provisions of the constitution in force. Key words: Serbia, human rights, separation of powers, rule of law.